2014
DOI: 10.4172/2157-7099.s4-010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of the Alimentary Tract of Two Reptilian Species the Lizard Scincus scincus and the Snake Natrix tessellata

Abstract: The ultrastructural difference of the alimentary tract of the insectivore, Scincus scincus and the carnivore, Natrix tesstellata was described by using scanning and transmission electron microscopy. The oesophagus of S. scincus with many prominent longitudinal folds while in N. tessellata it has many primary longitudinal folds and secondary ramification. The oesophageal epithelium of both species has numerous goblet cells. The mucosal epithelial cells in both species contain large nucleus, endoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Further, in the gastric mucosal glands, shallow and diminutive gastric pits were arranged in the dorsal surface extruding gastric secretions to the stomach lumen. These results agreed with Boonyoung (2017) and Abo-Eleneen et al (2014) whom reported similar distribution for gastric pores in the stomach of C. rynchops and Natrix tessellate , respectively. The gastric glands of P. sibilans were unique in that they possessed large oval-shaped mucous glands at the distal region of mucosa, the isthmus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further, in the gastric mucosal glands, shallow and diminutive gastric pits were arranged in the dorsal surface extruding gastric secretions to the stomach lumen. These results agreed with Boonyoung (2017) and Abo-Eleneen et al (2014) whom reported similar distribution for gastric pores in the stomach of C. rynchops and Natrix tessellate , respectively. The gastric glands of P. sibilans were unique in that they possessed large oval-shaped mucous glands at the distal region of mucosa, the isthmus.…”
Section: Discussionsupporting
confidence: 91%
“…Also, the mucosa was lined by pseudostratified columnar epithelium interspersed with goblet cells (Khamas & Reeves, 2011; Boonyoung et al, 2017). Notably, the mucosa bears numerous folia toward the luminal space (Abo-Eleneen et al, 2014). It was thus imperative that the highly folded esophageal mucosal folds, as evidenced by our histological and SEM investigations, played an essential role in the extraordinary esophageal distension when swallowing larger prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation